Diagnosis of venous thromboembolism in pregnancy. Issue 163 (March 2018) - Chan, Wee-Shian
Abstract: The diagnosis of deep vein thrombosis (DVT) and pulmonary embolism (PE) during pregnancy still relies on objective imaging. Ancillary testing such as clinical prediction rules and D-dimer testing may have a role in excluding both DVT and PE in these pregnant patients even as we await results from prospective management studies. The anatomical distribution of DVT in pregnancy differs from those in non-pregnant patient with a greater propensity for proximal iliac vein thrombosis. Using leg ultrasonography with compression maneuvers from the femoral vein to popliteal vein and doppler assessment of the iliac vein in a single examination, appears adequate in most pregnant women with suspected DVT, in excluding DVT. Further imaging with serial testing over 7 days would be indicated if isolated iliac DVT is suspected on initial imaging and if the patient has persistent symptoms. The diagnosis of PE in pregnant patients remains challenging. The use of a validated clinical prediction rule or D-dimer testing would be most useful here as it could subject fewer patients to diagnostic imaging which require ionizing radiation. However, until these ancillary tests are defined in prospective management studies, clinicians must rely on diagnostic imaging with either Ventilation-Perfusion Scan or Computed Tomography Pulmonary Angiography. The selection of these tests will rely largely on local availability and expertise. In the next few years, results from prospective management studies of DVT and PE diagnosis in pregnant women will become available as we move closer to diagnostic algorithms which will safely and accurately diagnose VTE while minimizing maternal and fetal risks of imaging. Highlights: Diagnosis of deep vein thrombosis (DVT) and pulmonary embolism during pregnancy relies primarily on Imaging Prospective studies confirmed the safety of whole leg ultrasound in excluding DVT during pregnancy despite the frequent occurence of ileofemoral DVT. The diagnosis of PE during pregnancy requires VQ scanning or CTPA; the selection of specific modality made after consideration of risks, test characteristics and availability. Currently clinical prediction rules and D-dimer testing should not be used as stand-alone tests to rule out DVT or PE.